VD_FINDINFO Jug / 2017 / 168 vom 8. Mai 2015 - VD Tribunal cantonal (2015)
GESTION FAUTIVE, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, DIRECTIVEINJONCTION | 165 ch. 1 CP, 44 al. 2 CP